Effective design of barrier enclosure to contain aerosol emissions from COVID‐19 patients. (20th April 2021) - Daniel, Dan; Lin, Marcus; Luhung, Irvan; Lui, Tony; Sadovoy, Anton; Koh, Xueqi; Sng, Anqi; Tran, Tuan; Schuster, Stephan C.; Jun Loh, Xian; Thet, Oo Schwe; Tan, Chee Keat
Abstract: Facing shortages of personal protective equipment, some clinicians have advocated the use of barrier enclosures (typically mounted over the head, with and without suction) to contain aerosol emissions from coronavirus disease 2019 (COVID‐19) patients. There is, however, little evidence for its usefulness. To test the effectiveness of such a device, we built a manikin that can expire micron‐sized aerosols at flow rates close to physiological conditions. We then placed the manikin inside the enclosure and used a laser sheet to visualize the aerosol leaking out. We show that with sufficient suction, it is possible to effectively contain aerosol from the manikin, reducing aerosol exposure outside the enclosure by 99%. In contrast, a passive barrier without suction only reduces aerosol exposure by 60%.